2002
DOI: 10.1212/wnl.58.3.422
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and autonomic nervous system function

Abstract: Migraineurs with disabling attacks may be prone to ANS hypofunction. These findings may suggest that ANS dysfunction either may be a risk factor for migraine headaches or be a consequence of frequent disabling attacks. Moreover, ANS dysfunction and migraine may share a common neural substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
123
1
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(141 citation statements)
references
References 38 publications
9
123
1
8
Order By: Relevance
“…20 Several clinical observations have found autonomic abnormalities in migraineurs compared to normal controls. [21][22][23][24] Periaqueductal gray (PAG) has been demonstrated to be dysfunctional in migraine. MRI imaging has determined that iron accumulation occurs in the PAG and that these changes correlate with duration of migraine frequency, are not independent of the presence of aura, and do not correlate with patient age.…”
Section: Commentsmentioning
confidence: 99%
“…20 Several clinical observations have found autonomic abnormalities in migraineurs compared to normal controls. [21][22][23][24] Periaqueductal gray (PAG) has been demonstrated to be dysfunctional in migraine. MRI imaging has determined that iron accumulation occurs in the PAG and that these changes correlate with duration of migraine frequency, are not independent of the presence of aura, and do not correlate with patient age.…”
Section: Commentsmentioning
confidence: 99%
“…Controversial theories about the cause and mechanisms of migraine range from experiments that show impaired brain energy metabolism [4], autonomic nervous system (ANS) hypofunction [5,6], brain cell hyperexcitability to low intracellular brain magnesium [7][8][9][10][11][12][13][14][15]. Once considered solely a vascular event, current research supports a combination of both neural and vascular causes [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The observed significant increase in sBP and unchanged dBP variables might be related with inhibition of PNS activity in M2 group patients. However, in some studies an opposite effect was found, such as, decreased sBP (Gudmundsson et al, 2006) and increased dBP (Shechter et al, 2002) at rest. These discrepancies may be associated with different ANS activity properties of migraine patients.…”
Section: Discussionmentioning
confidence: 93%